P470 Improving IBD-related pregnancy knowledge with a specialised preconception and pregnancy in IBD clinic. (16th January 2018) - Rodriguez, N; Ambrosio, L; Dieleman, L; Halloran, B; Kroeker, K I; Peerani, F; Wong, K; Fedorak, R N; Huang, V W
Abstract: Background: Inflammatory bowel disease affects women during their reproductive ages. IBD-related pregnancy knowledge has been reported to be low among women with IBD. We developed a specialised consultation clinic to educate and optimise the management of IBD. We aimed to assess IBD-related pregnancy knowledge among the patients referred to the clinic, and whether this clinic improves IBD-related pregnancy knowledge. Methods: Adult women with IBD who were seen in the Preconception and Pregnancy in IBD clinic, University of Alberta, were invited to participate. Demographics, reproductive history, IBD history, CCPKnow (Crohn's Colitis Pregnancy Knowledge) survey were obtained. The clinic offers protocolled education, clinical and objective disease monitoring throughout pregnancy and postpartum. Upon completion of follow-up (postpartum 3–12 months), CCPKnow was reassessed. Pre- and post-CCPKnow scores were compared using Student's t test for raw scores and chi-square test for rank. Results: A total of 99 (47 CD, 52 UC) mothers completed baseline surveys, CCPKnow 10 (IQR: 8–13); 22.2% poor, 36.4% adequate, 21.2% good, 20.2% very good. Of these, 37 (13 CD and 24 UC) completed postpartum CCPKnow surveys: 13.5% poor, 35.1% adequate, 16.2% good, 35.1% very good. Analysis showed that 21.6% had no change in score, 62.2% improved by at least 1 point, 62.2% remained in the same level, 29.7% improved their level. Of the seven patients with poor baseline knowledge, all seven improved CCPKnow score, three (42.9%) improved at least 1 level. Of the 14 patients with adequate baseline knowledge, eight (57.1%) improved CCPKnow score, four (28.6%) improved at least one level. Conclusions: A specialised consultation clinic improves IBD-related pregnancy knowledge among women with IBD. Further investigation into whether this protocolled clinic improves maternal and foetal clinical outcomes is currently in progress.